2016
DOI: 10.1002/htj.21254
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of a Louvered Fin Automotive Radiator Using Hybrid Nanofluid as Coolant

Abstract: This study deals with the theoretical enhancement of thermal performance using water-based (50/50) volume fraction of Fe 2 O 3 , CuO, TiO 2 , Ag, Cu in Al 2 O 3 hybrid nanofluids as coolants for a louvered fin automobile radiator. The effects on thermophysical properties and various performance parameters, i.e., heat transfer, effectiveness, and pumping power of hybrid nanofluids have been compared with water. Among all studied hybrid nanofluids, Al 2 O 3 -Ag/water hybrid nanofluid has higher effectiveness, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Sahoo et al 10 studied the augmentation of thermal performance utilizing the 50:50 volume ratio of different nanoparticles in water‐based Al 2 O 3 in combination with Cu, Ag, TiO 2 , and Fe 2 O 3 hybrid nanofluid as a coolant for a louvered fin vehicle radiator theoretically. Among these, alumina and silver/water hybrid nanofluid suggests effectiveness and heat transfer rate of 0.8% and 3%, respectively, for a concentration of 1% and temperature of 80°C.…”
Section: Introductionmentioning
confidence: 99%
“…Sahoo et al 10 studied the augmentation of thermal performance utilizing the 50:50 volume ratio of different nanoparticles in water‐based Al 2 O 3 in combination with Cu, Ag, TiO 2 , and Fe 2 O 3 hybrid nanofluid as a coolant for a louvered fin vehicle radiator theoretically. Among these, alumina and silver/water hybrid nanofluid suggests effectiveness and heat transfer rate of 0.8% and 3%, respectively, for a concentration of 1% and temperature of 80°C.…”
Section: Introductionmentioning
confidence: 99%
“…According to Sahoo et al [11], when hybrid nano uids were used as a radiator coolant, Al 2 O 3 + Ag/water-based hybrid nano uid showed greater e ciency in numerical terms. In the presence of the magnetic eld, Anjali Devi and Surya Uma Devi [12] concluded that hybrid nano uid (Cu-Al 2 O 3 /water) showed a higher heat transfer rate.…”
Section: Introductionmentioning
confidence: 99%
“…By virtue of their complementary thermophysical properties, hybrid nanofluids (i.e. nanofluids with multiple nanoparticle materials and/or geometries) were employed in forced convection heat transfer applications such as minichannel heat sinks (Kumar & Sarkar 2018), plate heat exchangers (Bhattad, Sarkar & Ghosh 2018 a ), corrugated plate evaporators (Bhattad, Sarkar & Ghosh 2018 b ), louvered fin automobile radiators (Sahoo, Ghosh & Sarkar 2017), shell-and-tube condensers (Singh & Sarkar 2018), milk chilling (Bhattad, Sarkar & Ghosh 2018 c ) and solar thermal collectors (Sarkar, Ghosh & Adil 2015).…”
Section: Introductionmentioning
confidence: 99%